2006
DOI: 10.1002/agr.20089
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wine attributes on region of origin equity: An analysis of the moderating effect of consumer's perceived expertise

Abstract: This research addresses the interaction between the components of brand. More specifically, the authors evaluate how the region of origin as a component of a wine brand adds value to a wine purchaser. Previous research suggests that the region of origin equity is significantly moderated by the other wine attributes with which it is combined on the wine label: commercial brand, level of price, type of bottler, grape variety. The authors test whether the moderating effects depend on self-perceived consumer exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
176
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(196 citation statements)
references
References 45 publications
15
176
2
3
Order By: Relevance
“…These results are in accordance with other studies from Old World countries (Angulo et al, 2000;Combris et al, 2000;Mtimet & Albisu, 2006;Perrouty et al, 2006;d'Hauteville et al, 2007;Barreiro et al, 2008;Hertzberg & Malorgio, 2008;Bernabèu et al, 2012). Thus, there are clear indications that this attribute should have more emphasis in communications with them.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in accordance with other studies from Old World countries (Angulo et al, 2000;Combris et al, 2000;Mtimet & Albisu, 2006;Perrouty et al, 2006;d'Hauteville et al, 2007;Barreiro et al, 2008;Hertzberg & Malorgio, 2008;Bernabèu et al, 2012). Thus, there are clear indications that this attribute should have more emphasis in communications with them.…”
Section: Discussionsupporting
confidence: 83%
“…However, grape variety, country of origin, "someone recommended it" and "I tasted the wine previously" are the most relevant and preferred wine attributes by consumers from New World countries such as Australia, New Zealand and the United States (Hall et al, 2001;Loureiro, 2003;Schamel & Anderson, 2003;Charter & Pettigrew, 2006;Lockshin et al, 2006;Boudreaux & Palmer, 2007;Jarvis et al, 2007;Johnson & Bruwer, 2007;Hollebeek et al, 2007;Veale, 2008;Kolyensikova et al, 2008;Cohen, 2009;Cohen et al, 2009;Goodman, 2009). Finally, some studies have found that brand name, label design, price and "it won a medal/award" had a similar perceived relevance by Old World and New World wine consumers (Angulo et al, 2000;Hall et al, 2001;Skuras & Vakrou, 2002;Thomas & Pickering, 2003;Lockshin et al, 2006;Martinez-Carrasco et al, 2006;Mtimet & Albisu, 2006;Perrouty et al, 2006;Boudreaux & Palmer, 2007;d'Hauteville et al, 2007;Jarvis et al, 2007;Johnson & Brower, 2007;Barreiro et al, 2008;Bernabèu et al, 2008;Hertzberg & Malorgio, 2008;Kolyesnikova et al, 2008Casini & Corsi, 2009Cohen, 2009;Cohen et al, 2009;Goodman, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the results allow us to conclude that those consumers with less knowledge about wine present a stronger link between the image formed in their minds about the region as a wine producer and their perception of the quality of its wines. These results are contrary to the conclusions reached by Perrouty et al (2006), Atkin & Johnson (2010), and Atkin & Newton (2012). Those authors found that consumers who are more expert and involved in their purchase of wine give greater importance to information about its ROO in their purchasing process.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies such as those by Perrouty et al (2006), Atkin & Johnson (2010), and Atkin & Newton (2012) have shown that consumers who are more expert and involved in the purchase of wine give greater importance to the ROO information in their purchasing process. Other studies that have included this variable in the general place-of-origin context are those of Insch & McBride (2004) and Srinivasan et al (2004).…”
Section: Proposal Of a Model Of The Roo Effectmentioning
confidence: 99%
See 1 more Smart Citation